Opening the Black Box of Scholarly Communication Funding: A Public Data Infrastructure for Financial Flows in Academic Publishing. Issue 1 (11th April 2016) - Lawson, Stuart; Gray, Jonathan; Mauri, Michele
'Public access to publicly funded research' has been one of the rallying calls of the global open access movement. Governments and public institutions around the world have mandated that publications supported by public funding sources should be publicly accessible. Publishers are experimenting with new models to widen access. Yet financial flows underpinning scholarly publishing remain complex and opaque. In this article we present work to trace and reassemble a picture of financial flows around the publication of journals in the UK in the midst of a national shift towards open access. We contend that the current lack of financial transparency around scholarly communication is an obstacle to evidence-based policy-making – leaving researchers, decision-makers and institutions in the dark about the systemic implications of new financial models. We conclude that obtaining a more joined up picture of financial flows is vital as a means for researchers, institutions and others to understand and shape changes to the sociotechnical systems that underpin scholarly communication. A correction article relating to the cost of journal subscription in Austria can be found here:http://dx.doi.org/10.16995/olh.107